TREES VEGETATION DIVERSITY IN PT ARUN NGL HOUSING, LHOKSEUMAWE, ACEH PROVINCE - Iqbar Iqbar (Jurnal Natural, 2016)
The research about trees vegetation diversity in PT Arun NGL area had been done in December 2012. The objective of the research was to calculate the trees vegetation diversity index. The data had been collected in nine belt transects by length 400 m and  400 m2  (10 m x 40 m) plots  for each belt transect. The collecting data was  including name of species, family, density, frequency and  dominancy.  The data was analyzed to get important value and diversity index. The result showed that there were 39 tree species belongs to 23 families found in the research area.  There were three dominant species namely; Pterocarpus indicus,  Pithecelobium dulce, dan Leucaena leucocephala which had higher important value than others species that lead  influencing the ecosystem. The trees diversity index in this area was about 3,3 which interpreted this area has high diversity index. Moreover, the plants were planted in PT Arun NGL Housing Area have another function as reducing pollutant material in the air.